Comparative Analysis of Open Position and Hedging Techniques in The Import Value Management of PT Pertamina (Persero) - Herlinda Fitri Febriyanti; Silvi Delfiani; Irdha Yusra (Financial Management Studies, 2022)
Fluctuations in currency exchange rates result in the value of the company's debt of import payment to be uncertain because any time may be changing. Companies can do hedge techniques to protect the value of the import debt or leave it in a state without the hedge. The purpose of this research is to know the value of the company's debt of import when using forward contract hedge, money market hedge, and open position and choose the most efficient method. This research uses import transaction data of PT Pertamina (Persero). The analysis technique used is the Wilcoxon Signed Ranks Test and calculation with Microsoft Excel. From this research, it is found that there is no difference in the average value of the company's import debt when using forward contract hedging technique with an open position. But there is a difference when using money market hedge technique with the open position. The result of the research is the value of import debt is more efficient when the company uses open position or without the hedge.